2011
DOI: 10.1016/j.ijdevneu.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fetal response to maternal speech using a noninvasive functional brain imaging technique

Abstract: Evidence for cortical sensory activation in the human fetus at the beginning of the third trimester of pregnancy was provided in a recent imaging study. Although hearing is functional before birth, it is not clear whether recognition of the mother's voice is learned in utero or rapidly following delivery. We developed an original fMRI procedure that allows for the specific exploration of fetal brain response to auditory stimuli. This procedure provides the first in vivo evidence for the development of maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 15 publications
1
50
0
1
Order By: Relevance
“…However, similar to visual studies, fMRI research featured smaller sample sizes (3-15) and more restricted age ranges (1-4 weeks) when contrasted with fMEG. More sophisticated auditory stimuli have also been used, ranging from Spanish guitar music (Moore et al, 2001) to the discrimination of familiar and unfamiliar speech (Jardri et al, 2012). There was a consistent report of unilateral, left temporal activation bias (Jardri et al, 2008(Jardri et al, , 2012.…”
Section: Auditory Processing-fmrimentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar to visual studies, fMRI research featured smaller sample sizes (3-15) and more restricted age ranges (1-4 weeks) when contrasted with fMEG. More sophisticated auditory stimuli have also been used, ranging from Spanish guitar music (Moore et al, 2001) to the discrimination of familiar and unfamiliar speech (Jardri et al, 2012). There was a consistent report of unilateral, left temporal activation bias (Jardri et al, 2008(Jardri et al, , 2012.…”
Section: Auditory Processing-fmrimentioning
confidence: 99%
“…More sophisticated auditory stimuli have also been used, ranging from Spanish guitar music (Moore et al, 2001) to the discrimination of familiar and unfamiliar speech (Jardri et al, 2012). There was a consistent report of unilateral, left temporal activation bias (Jardri et al, 2008(Jardri et al, , 2012. However, one study reported mixed results with 3 participants displaying a left bias and 2 exhibiting a right (Moore et al, 2001).…”
Section: Auditory Processing-fmrimentioning
confidence: 99%
“…auditory | brain | mother's voice | heartbeat | preterm newborns O ne of the first acoustic stimuli we are exposed to before birth is the voice of the mother and the sounds of her heartbeat. As fetuses, we have substantial capacity for auditory learning and memory already in utero (1)(2)(3)(4)(5), and we are particularly tuned to acoustic cues from our mother (6)(7)(8)(9). Previous research suggests that the innate preference for mother's voice shapes the developmental trajectory of the brain (10,11).…”
mentioning
confidence: 99%
“…Studies carried out on babies in gestational stages, using MRI scan 11 and checking their heart rate 12 , verified selective cortical processing what indicates the formation of neural network in the third quarter of pregnancy. These studies imply that babies prove to be able to recognize their mother's voice from an early age, and this fact can indicate that, therefore, there is learning as far back as the uterine life.…”
Section: Review Of Literaturementioning
confidence: 76%